ANALISIS KESELAMATAN LALU LINTAS DI AREA SIMPANG BAWEN - Lita, Eleonora Jade Marsha; Bagus Hario Setiadji; Bambang Haryadi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
Simpang Bawen area connects Semarang with surrounding cities such as Salatiga, Surakarta, and Yogyakarta. Between 2017-2023, 98 accidents were recorded starting from Hortimart Agro Center to Simpang Exit Tol Bawen. This study aims to analyze the characteristics of traffic accidents, contributing geometric and operational design factors, and recommendations for safety improvements. The in-depth analysis method in qualitative descriptive research was used with accident data from the Semarang Police Traffic Unit and supporting data from the Central Java-Yogyakarta National Road Implementation Center. Field surveys were conducted to observe location conditions. The analysis was carried out by dividing the research location into five zones. The results of the analysis showed that the most frequent accident types varied in each zone and were dominated by motorcycles and heavy vehicles. Accidents occurred in sunny weather with moderate severity and were caused by non-priority behavior. Recommendations for improvement include closing U-turns, adding rumble strips, building flyovers, installing traffic lights, enforcing traffic laws, and improving street lighting.